A randomized sham-controlled trial of high-dosage accelerated intermittent theta burst rTMS in major depression: study protocol - Michelle S. Goodman; Fidel Vila-Rodriguez; Melanie Barwick; Matthew J. Burke; Jonathan Downar; Jonathan Hunter; Tyler S. Kaster; Yuliya Knyahnytska; Paul Kurdyak; Robert Maunder; Kevin Thorpe; Alisson P. Trevizol; et al. (BMC Psychiatry, 2024)
Abstract Background Intermittent theta burst stimulation (iTBS), a novel form of repetitive transcranial magnetic stimulation (rTMS), can be administered in 1/10th of the time of standard rTMS (~ 3 min vs. 37.5 min) yet achieves similar outcomes in depression. The brief nature of the iTBS protocol allows for the administration of multiple iTBS sessions per day, thus reducing the overall course length to days rather than weeks. This study aims to compare the efficacy and tolerability of active versus sham iTBS using an accelerated regimen in patients with treatment-resistant depression (TRD). As a secondary objective, we aim to assess the safety, tolerability, and treatment response to open-label low-frequency right-sided (1 Hz) stimulation using an accelerated regimen in those who do not respond to the initial week of treatment. Methods Over three years, approximately 230 outpatients at the Centre for Addiction and Mental Health and University of British Columbia Hospital, meeting diagnostic criteria for unipolar MDD, will be recruited and randomized to a triple blind sham-controlled trial. Patients will receive five consecutive days of active or sham iTBS, administered eight times daily at 1-hour intervals, with each session delivering 600 pulses of iTBS. Those who have not achieved response by the week four follow-up visit will be offered a second course of treatment, regardless of whether they initially received active or sham stimulation. Discussion Broader implementation of conventional iTBS is limited by the logistical demands of the current standard course consisting of 4–6 weeks of daily treatment. If our proposed accelerated iTBS protocol enables patients to achieve remission more rapidly, this would offer major benefits in terms of cost and capacity as well as the time required to achieve clinical response. Trial registration ClinicalTrials.gov Identifier: NCT04255784.